Empowering the Exclusionary Rule: Using suppression motion data to improve police searches and searches in the United States - Nir, Esther (International journal of police science & management, 2020)
The Exclusionary Rule (i.e. a U.S. Supreme Court created rule that bars evidence, obtained in violation of a defendant’s constitutional rights, from being used by the prosecution at trial) remains a highly controversial measure, with questionable ability to deter unreasonable searches and seizures. In fact, many decades since its enactment, allegations of unconstitutional stops, searches, and seizures continue to plague police departments across the United States. Examining these allegations is a critical step toward assessing police compliance with constitutional mandates and developing needed corrective measures. Content analyses of suppression motions (brought by criminal defendants to exclude incriminating evidence from trial based on allegations of unconstitutional police action) and hearings, conducted in an urban U.S. city, demonstrate how these data provide unique information from multiple perspectives (e.g. defense, prosecution, court, lay and police witnesses)—involving pretexual stops, defendant targeting, and over-reaching searches—that may be used to develop police training protocols, support early intervention systems, and improve local patterns of officer behavior. In this way, data generated by the Exclusionary Rule may not only empower the rule to achieve its intended purpose of enforcing constitutional protections in the United States, but also provide a framework of police accountability (by demonstrating the utility of court data) that may improve police searches and seizures in other countries.